2012
DOI: 10.5455/jib.20120501030110
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia As A Marker For Preterm Labour And Its Association With Socio Economic Status.

Abstract: The aim of our investigation was to study the Serum magnesium levels in preterm labour and to compare these values with those patients who had a term delivery ,to find associated signs and symptoms and to suggest nutritional correction of prognostic value Methods:-A case-control study was carried out to evaluate serum magnesium levels and associated symptoms in women with preterm labour (28-36 weeks) and compare them with patients in same gestational age who delivered at term(37-40 weeks). Results:-Patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…8,9 However, it was lower in preterm group as compared to study conducted by Bhat et al, (28.63 years). 7 The difference can be explained due to early age of marriage and lesser use of contraceptives methods in our study.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…8,9 However, it was lower in preterm group as compared to study conducted by Bhat et al, (28.63 years). 7 The difference can be explained due to early age of marriage and lesser use of contraceptives methods in our study.…”
Section: Discussionmentioning
confidence: 57%
“…Bhat et al, found patients with preterm labour belonging to low socioeconomic class were significantly higher than the middle and higher socioeconomic classes (58% in preterm labour patients and 45% in term, p<0.05). 7 Mahmoud et al, also found that in preterm labour group lower socioeconomic class was significantly higher than the middle and upper socioeconomic classes. 8 Patients belonging to low socioeconomic classes have stressful lifestyle, inaccessible medical care and diet deficient in micronutrients including magnesium.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations